ANALISIS MENU DENGAN METODE MENU ENGINEERING UNTUK MELIHAT TINGKAT KEPOPULERAN, KLASIFIKASI DAN KONTRIBUSI KEUNTUNGAN MENU DI SEJALAN COFEEHOUSE KABUPATEN SOLOK - Asty, Wina; Mirza Hanafiah, Siti; Kumala, Vina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: Sejalan coffeehouse that has been around since 2019, this cafe provides coffee and non-coffee drinks, while for food it provides from main courses to desserts and snacks. Currently, the number of menus served to consumers is too large, including 60 menu items. Of the menus provided, not all menus are popular or are of interest to consumers, and this is not effective. improvement to better. Meanwhile, according to (Ayodya, 2013) that in the food and drink industry (restaurants, restaurants, cafes) the menu is very influential on sales and marketing which makes a person or group to visit again, by evaluating the menu we can identify the performance of each menu from various aspects starting from the level of popular menu, menu categorization to the level of profit contribution provided by each food and beverage menu at Sejalan Coffehouse. In evaluating the menu, the engineering method was used (menu engineering) by analyzing 60 food and beverage menu items Sejalan coffeehouse. From the results of the Menu research at the level of popularity and profit with 6 types of menu groups with 60 menu items, namely the Drink Espresso Based menu type has 9 menu items that have a popularity level (MM%) of 8%, the Drink Signature menu type has 4 menu items that have the popularity level (MM%) is 18%, the Drink Smoothies menu type has 11 menu items which have a popularity level (MM%) of 6% , the Drink Squash and Frappe menu type has 4 menu items which have a popularity level (MM%) of 18 %, the Snacks menu type has 11 menu items which have a popularity level (MM%) of 6%, and the Food menu type (main course) has 21 menu items which have a popularity level (MM%) of 3%. Meanwhile, of the 60 menu items, 22 menu items can be categorized in the Star position, 19 menus are in the Plowhorse category, the Puzzle category is divided into 13 menu items, while those included in the Dog category are divided into 6 menu items.Keywords: Menu,Menu Enginerring, Restouran.